2012
DOI: 10.1111/j.1600-6143.2011.03981.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Geographic Variation in Mortality in the Context of Organ Donation

Abstract: Mortality data demonstrate that deaths by neurologic criteria of people who are likely to be suitable deceased donors are not evenly distributed across the nation. These deaths are correlated with eligible deaths for organ donation. Regional availability of organs is affected by deaths which should be accounted for in the organ allocation system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…We employed several assumptions to develop our estimate of the possible donor supply, albeit based on published data that could be extrapolated to our population of patients dying in an intensive care unit potentially eligible to be a deceased donor. We estimated an average of 13 985 possible DNDD donors, which we feel confident is close to the true donor potential for two reasons: (1) the estimates of the possible donor supply obtained using administrative data matched closely with patient-level data obtained from chart review from two OPOs; and (2) a large multiyear study that utilized medical record review of patients in 434 hospitals across 36 OPOs between 1997 and 1999 suggested the DNDD donor potential may be as high as 13 800 per year (29)(30)(31). Given increases in the number of deaths that could lead to donation (i.e.…”
Section: Discussionmentioning
confidence: 70%
“…We employed several assumptions to develop our estimate of the possible donor supply, albeit based on published data that could be extrapolated to our population of patients dying in an intensive care unit potentially eligible to be a deceased donor. We estimated an average of 13 985 possible DNDD donors, which we feel confident is close to the true donor potential for two reasons: (1) the estimates of the possible donor supply obtained using administrative data matched closely with patient-level data obtained from chart review from two OPOs; and (2) a large multiyear study that utilized medical record review of patients in 434 hospitals across 36 OPOs between 1997 and 1999 suggested the DNDD donor potential may be as high as 13 800 per year (29)(30)(31). Given increases in the number of deaths that could lead to donation (i.e.…”
Section: Discussionmentioning
confidence: 70%
“…7,8 By this logic, using eligible deaths as a denominator to which overall donor yield is compared is a fair measure of OPO performance, as it accounts for these population differences over which an OPO has no control. 7,8 By this logic, using eligible deaths as a denominator to which overall donor yield is compared is a fair measure of OPO performance, as it accounts for these population differences over which an OPO has no control.…”
Section: It Has Been Reported That Variation In Eligible Deaths Betweenmentioning
confidence: 99%
“…Allocation Given the reality in which the availability of organs is such that there will always be scarcity (even if everyone who could donate upon death did so, which is only 0.5 % of all deaths (Sheehy et al 2012)), it is essential to ensure that all of those who can donate do so. To accomplish this it is essential that all who may be asked to donate believe that if they need a transplant they will have an equal opportunity to receive one.…”
Section: Separation From Transplantationmentioning
confidence: 99%
“…And while perfect-match kidneys may travel across the country and the sickest liver recipient in a broader region may receive the next organ, local-first remains the basis of organ sharing (Graham 2006). A problematic consequence of this historic allocation sys-tem is that potential organ donors are not uniformly distributed across the US, with the some regions having 40-50 % higher potential and concordant 40-50 % shorter waiting times for transplant (Sheehy et al 2012).…”
Section: Introductionmentioning
confidence: 99%